Vehicle mobility on highly organic soils. (December 2021) - Parker, Michael; Stott, Alexander; Bodie, Mark; Frankenstein, Susan; Shoop, Sally
Highlights: Mobility codes do not accurately represent modern military mobility on organic soil. Low ground pressure vehicles perform better on organic soil. Organic soils have a wide variability of soil and vegetation conditions. Abstract: Current political climates have generated a renewed interest in the northern regions of the world. These areas are known to have soft marshy peat, highly organic soils, and harsh winter climates. Current capabilities for vehicle mobility modeling on this terrain is limited and existing studies do not include contemporary military vehicles. This work presents mobility experiments of modern military vehicles at multiple field sites containing peat or highly organic soils that can be used to improve mobility modeling on these soils. Field experiments are being conducted during multiple seasons, including winter, spring, and summer. The vehicle traction, motion resistance, and hard surface rolling resistance of an instrumented High Mobility Multipurpose Wheeled Vehicle (HMMWV) and a Small Unit Support Vehicle (SUSV) were examined. The first is a common multi-purpose vehicle and the second is a vehicle designed to operate in these types of environments. This data set will provide the basis for model development and validation for vehicle mobility in highly organic soils.